Exploring the relationship between problem-solving ability and mathematical disposition in 10-11 year’s old students using model-eliciting activities - Wahyuningrum, Endang; Bonyah, Ebenezer; Yumiati, Yumiati; Kartono, Kartono; Wijayanti, Nina (Universitas Islam Raden Intan Lampung, INDONESIA, 2024)
Background: Problem-solving ability and mathematical disposition are essential skills in mathematics education, particularly in developing critical thinking and practical application among students. Model-Eliciting Activities (MEAs) have been introduced as an instructional approach aimed at enhancing these skills by integrating real-world problems into learning. However, the effectiveness of MEAs in establishing a significant relationship between problem-solving ability and mathematical disposition remains unclear, necessitating further investigation.Aim: This study aims to analyze the association between problem-solving ability and mathematical disposition after implementing Model-Eliciting Activities (MEAs) in instruction.Method: This study employed a quantitative design with a cross-sectional approach, involving 30 fifth-grade students from SDN 02 Bojongsari, Depok, Indonesia, as participants. Data were collected using a problem-solving ability test and a mathematical disposition questionnaire. Subsequently, the data analysis was carried out using chi-square tests.Result: The results of the study showed that the χ2 value of 0.731 is less than α = 0.947, indicating that there is no significant relationship between mathematical problem-solving ability and mathematical disposition.Conclusion: The study concluded that no association was found between problem-solving ability and mathematical disposition among elementary school students after implementing MEAs in instruction. Additionally, although there is a tendency for students with a high mathematical disposition to demonstrate stronger problem-solving skills, this correlation is not strong enough to be considered significant